COMPARISON OF ENTREPRENEURIAL PERSONALITY CHARACTERISTICS OF MALE AND FEMALE ENTREPRENEURS - Ece, Süreyya (Journal of Yasar University, 2019)
In the studies on entrepreneurship, it has been claimed that there are entrepreneurial personality characteristics lead individuals become entrepreneur. Uncertainty tolerance, achievement, dominance, affiliation and autonomy are among the foreground entrepreneurial personality characteristics. The purpose of the study is comparing male and female entrepreneurs in terms of entrepreneurial personality characteristics. The data of the research were obtained from 30 male and 30 female entrepreneurs from Şırnak province through survey. Discriminant analysis was applied to determine whether male and female participants differed in their entrepreneurial personality characteristics. Findings of the analysis showed that the female entrepreneurs’ uncertainty tolerance was lower than that of the male entrepreneurs, but other entrepreneurial personality traits were found to be higher. According to these results, it can be said that female entrepreneurs have a high entrepreneurial potential. It is thought that especially if economic support is provided women entrepreneurs will be able to make successful initiatives.
Keywords: Girişimci Kişilik Özellikleri; Kadın Girişimciler; Erkek Girişimciler